Розвиток фінансового ринку як фактор економічної безпеки України - Борисюк, Олена Володимирівна; Дацюк-Томчук, Марія Богданівна; Ліповська-Маковецька, Наталія Іванівна; Borysiuk, Olena V.; Datsiuk-Tomchuk, Mariia B.; Lipovska-Makovetska, Nataliіa I. (My University, 2019)
The financial market should become one of the main mechanisms for the mobilization of free resources for economic development and the formation of reliable savings instruments for the population. This can be achieved by stabilizing the foreign exchange market, reducing and maintaining the level of inflation at acceptable levels for the development of the economy, stabilizing the work of the financial sector, restoring public confidence in the institutions of the financial market.
Development of financial market as factor of economic security of Ukraine
Keywords: фінансовий ринок; економічна безпека України; банківський сектор; страховий сектор